Supply chain alignment as process: contracting, learning and pay-for-performance. Issue 3 (5th March 2018) - Selviaridis, Kostas; Spring, Martin
Abstract : Purpose: The purpose of this paper is to understand how buyers and suppliers in supply chains learn to align their performance objectives and incentives through contracting. Design/methodology/approach: Two longitudinal case studies of the process of supply chain alignment were conducted based on 26 semi-structured interviews and 25 key documents including drafts of contracts and service level agreements. Findings: The dynamic interplay of contracting and learning contributes to supply chain alignment. Exchange-, partner- and contract framing-specific learning that accumulates during the contracting process is used to (re)design pay-for-performance provisions. Such learning also results in improved buyer-supplier relationships that enable alignment, complementing the effect of contractual incentives. Research limitations/implications: The study demonstrates that the interplay of contracting and learning is an important means of achieving supply chain alignment. Supply chain alignment is seen as a process, rather than as a state. It does not happen automatically or instantaneously, nor is it unidirectional. Rather, it is a discontinuous process triggered by episodic events that requires interactive work and learning. Practical implications: Development of performance contracting capabilities entails learning how to refine performance incentives and their framing to trigger positive responses from supply chain counterparts. Originality/value: The paper addresses supply chain alignment as a process. Accordingly, it stresses some important features of supply chain alignment.